2020
DOI: 10.1021/acschemneuro.9b00691
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Optimization, and Evaluation of Methoxy Poly(ethylene glycol)-co-Poly(ε-caprolactone) Nanoparticles Loaded by Rivastigmine for Brain Delivery

Abstract: The objective of this study was to formulate and investigate the neuropharmacokinetics and pharmacodynamics of rivastigmine (Riv) loaded methoxy poly­(ethylene glycol)-co-poly­(ε-caprolactone) (MPEG-PCL) nanoparticles (Riv-NPs) in rats after IV administration. The MPEG-PCL was synthesized via ring-opening polymerization of ε-caprolactone by MPEG and used to prepare Riv-NPs by the nanoprecipitation method. Response surface D-optimal design was applied to optimize Riv-NPs drug delivery system. The optimized form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Acetylcholinesterase inhibitor PEG-b-PCL The PK study in rats indicated that the brain uptake of rivastigmine-loaded micelle was significantly higher than that of the free drug. Pharmacodynamic studies using the Morris water maze test confirmed that faster regain of memory loss with micellar formulation when compared to the free drug solution [330]. .…”
Section: Rivastigminementioning
confidence: 80%
“…Acetylcholinesterase inhibitor PEG-b-PCL The PK study in rats indicated that the brain uptake of rivastigmine-loaded micelle was significantly higher than that of the free drug. Pharmacodynamic studies using the Morris water maze test confirmed that faster regain of memory loss with micellar formulation when compared to the free drug solution [330]. .…”
Section: Rivastigminementioning
confidence: 80%
“…To allow the modelling of linear, quadratic and two-way interaction effects of each factor with a minimal amount of experimental runs, a D-optimal split-plot experimental design with three levels for each factor was created using the DoE functionality of JMP Pro 14 software (SAS). Similar approaches have been taken by several authors to optimize NP formulations (Günday Türeli, et al 2016;Mohamadpour, et al 2020;Tahir, et al 2017).…”
Section: Experimental Designmentioning
confidence: 96%
“…Changing the molar mass or coating it with alternative polymers, such as PLA, might alleviate this problem [ 111 ]. Hence, it has been used as a suitable coating in the design of the brain delivery system [ 52 , 112 , 113 ].…”
Section: Coating Polymersmentioning
confidence: 99%